Antimicrobial activity of trisodium phosphate and sodium hypochlorite against Salmonella biofilms on abiotic surfaces with and without soiling with chicken juice - Sarjit, A.; Dykes, Gary (Pergamon, 2017)
Salmonella is a major foodborne pathogen of public health concern and is often associated with contaminated poultry. This pathogen can adhere to surfaces in food processing facilities leading to the formation of biofilms. Antimicrobial treatments during poultry processing represents a mechanism to control biofilms. This study investigated the effect of trisodium phosphate (TSP) and sodium hypochlorite (SH) on biofilms of two strains each of S. Enteritidis, two strains each of S. Typhimurium, and one strain of S. Senftenberg on stainless steel, glass and polyurethane. Biofilms were grown on surfaces without soiling or with soiling (chicken juice) applied before or after biofilm formation. Biofilms on all surfaces were treated (TSP: 8, 10 and 12% (w/v), pH 11.5 and SH: 40, 50 and 60 ppm, pH 5.5) for 10 min. Untreated controls and controls using water were included for all the experiments. Bacterial numbers in biofilms were determined by plating on thin layer xylose lysine deoxycholate medium. If numbers were below the limit of detection (1.81 log cfu/cm2) biofilms were enriched in buffered peptone water before plating to establish the presence of live cells. All TSP treatments rendered cells uncountable except for four specific combinations of bacteria, soiling and surfaces at the 8% treatment level. In cases where numbers were below detection, live cells were present for some combinations of bacteria, soiling and surfaces at all TSP levels. All SH treatments rendered cells uncountable on unsoiled stainless steel and glass for all strains. In these cases strains were alive at 40 ppm on stainless steel. On polyurethane cells were only uncountable for one strain at 60 ppm and live cells were detected in this case. All SH treatments resulted in countable numbers of cells for all strains on soiled surfaces. Trisodium phosphate has strong potential as a sanitizer to reduce biofilm formation by Salmonella spp. on abiotic surfaces during poultry processing.